The Use of Extracorporeal Membrane Oxygenation Systems in Severe Accidental Hypothermia After Drowning: A Centre Experience. Issue 2 (March 2016) - Weuster, Matthias; Haneya, Assad; Panholzer, Bernd; Klüter, Tim; van der Brelie, Michael; van Laak, Ulrich; Cremer, Jochen; Haake, Nils
Abstract : Cardiopulmonary failure because of drowning with accidental hypothermia (AH) remains a major task for emergency care physicians. In this case series, we describe our experience in nine patients with cardiopulmonary failure after drowning with AH less than 35°C, who were provided on an emergency basis with extracorporeal life support (ECLS) system or extracorporeal membrane oxygenation (ECMO). Conservative rewarming methods are not considered for this study. Preclinical conditions and protocols were gathered. Surgical reports and clinical data sets were collected. Median age was 24 years (range, 6–75 years). Six patients were male. Climatic conditions mostly showed cold to frosty weather. All cases had different preclinical rescue procedures. They reached the emergency department under cardiopulmonary resuscitation (CPR). Indications for ECLS were cardiac arrest, and in one case, pulmonary failure. Mean CPR duration was 60 min (range: 15–120 min). Before implantation, the median pH value was 6.9. Two patients could be successfully weaned from the systems. Cause of death was severe neurologic damage in six patients and cardiac failure in one patient. The use of ECLS/ECMO is a therapy option for a small range of patients with cardiopulmonary failure because of drowning with AH. Nevertheless, the interval of preclinical rescue remains extensively long.